Synaptic tagging: homeostatic plasticity goes Hebbian. (13th September 2022) - Colameo, David; Schratt, Gerhard
Abstract : Distinct plasticity mechanisms enable neurons to effectively process information also when facing global perturbations in network activity. In this issue of The EMBO Journal, Dubes et al (2022) provide a molecular mechanism whereby individual synapses during periods of chronic inactivity are "tagged" for future strengthening. These results lend further support to the idea that local, nonmultiplicative mechanisms play an important role in homeostatic synaptic plasticity as has been demonstrated for Hebbian‐like synaptic plasticity. Abstract : Recent work shows how global perturbations in network activity can also act locally to support future synaptic activity.